The features of the Linguacultural Concept of ̓ Clothing ̓ in the Serbian Speech of Prizren - Milosavlјević Tanja (Bulletin of the Institute of Ethnography SASA, 2022)
The concept of ’clothing’ represents one of the key mental, cultural and linguistic constants in the conceptosphere, which makes it a current subject matter of scien tific study, considering that on the one hand, clothing has particular importance in the everyday life of representatives of various society, and on the other, that it has from as far back as we can remember, been a means of conceptualizing the world by reflecting the objective reality and realizing various social functions – the aes thetic, utilitarian, gender, ethnic, ritualistic. The reconstruction of the concept from the linguacultural aspect includes an analysis of the elements of its verbal explica tion and the interpretation on the linguistic image of the world of a particular lin guistic or speech community. Our task is to describe the concept of clothing of the Serbian speech of Prizren using lexical units which contain a cultural component of meaning and reflect the features of traditional culture, view of the world, and the mentality of the Serbian linguistic persona from the end of the 19th and begin ning of the 20th century. Based on the material from the Zbirka reči iz Prizrena by Dimitrije Čemerikić we will present a structure of the concept with the lexical dom inants of obúklo, rúba, tе́še, which include qualificatives that complete the image of the everyday, special occasion, and ritual apparel in the life of Prizren; activities re lated to clothing; individual items of men’s and women’s clothing; ornaments as an important component of the aesthetic experience of the old inhabitants of Prizren. The conceptualization of clothing in the consciousnesses of the Prizren linguistic persona is reflected in the corresponding lexical units, and manifests the cultural and value dominants of an urban peripheral multinational, multicultural, and mul tilingual community in a certain historical period of time, reflecting the impact and permeating effect of elements of the culture of clothing of various ethnic groups.